The Relationship of Learning Motivation to Student Learning Outcomes in Physical Education Learning During the Covid-19 Pandemic - M. Fransazeli Makorohim; Mimi Yulianti; Rika Sebriani (International Conference on Science, Education, and Technology, 2021)
The purpose of the study was to see the relationship between student learning motivation and student learning outcomes in physical education learning during the covid-19 pandemic. This type of research is correlational with a quantitative approach. The population in this study were students of class X SMA YLPI Pekanbaru, amounting to 47 students. The sampling technique in this study used a total sampling technique. Data were collected with a research instrument in the form of a questionnaire (questionnaire).The results showed that there was a significant and significant relationship between learning motivation and student learning outcomes in physical education learning during the covid-19 pandemic. By calculating the correlation r_count 0,528 > r_table=0,288 then there is a significant relationship with the results of the coefficient of determination of motivation giving a value of 28% on the learning outcomes of physical education in students and the remaining 72% due to other factors.